Hepatotoxicity by herbs: a practical review of a neglected disease - Donet, Jean A. (2017)
Herbs are commonly used worldwide for the treatment of various diseases, constituting a multi-billion dollar market. Unfortunately, hepatotoxicity induced by herbs is also common. The true incidence and prevalence are not known. There is need for more strict regulations andexperimental and pre-clinical studies regarding its efficacy and safety. There is no gold standard for the diagnosis of herbs-induced liver injury (HILI) and it constitutes a diagnostic challenge for the clinician, whereestablishing causality could be cumbersome. Clinical presentation varies from asymptomatic cases with mildly abnormal liver tests to fulminant liver failure requiring liver transplantation. In this review, we will discuss the epidemiology, clinical manifestations, challenges and diagnostic approach of HILI and will also present some exemplary cases from the University of Miami, Division of Hepatology.